Natural Polymeric Scaffolds in Bone Regeneration - Filippi, Miriam; Born, Gordian; Chaaban, Mansoor; Scherberich, Arnaud (Frontiers in Bioengineering and Biotechnology, 2020)
Despite considerable advances in microsurgical techniques over the past decades, bone tissue remains a challenging arena to obtain a satisfying functional and structural restoration after damage. Through the production of substituting materials mimicking the physical and biological properties of the healthy tissue, tissue engineering strategies address an urgent clinical need for therapeutic alternatives to bone autografts. By virtue of their structural versatility, polymers have a predominant role in generating the biodegradable matrices that hold the cells in situ to sustain the growth of new tissue until integration into the transplantation area (i.e. scaffolds). As compared to synthetic ones, polymers of natural origin generally present superior biocompatibility and bioactivity. Their assembly and further engineering give rise to a wide plethora of advanced supporting materials, accounting for systems based on hydrogels or scaffolds with either fibrous or porous architecture. The present review offers an overview of the various types of natural polymers currently adopted in bone tissue engineering, describing their manufacturing techniques and procedures of functionalization with active biomolecules, and listing the advantages and disadvantages in their respective use in order to critically compare their actual applicability potential. Their combination to other classes of materials (such as micro and nanomaterials) and other innovative strategies to reproduce physiological bone microenvironments in a more faithful way are also illustrated. The regeneration outcomes achieved in vitro and in vivo when the scaffolds are enriched with different cell types, as well as the preliminary clinical applications are presented, before the prospects in this research field are finally discussed. The collection of studies herein considered confirms that advances in natural polymer research will be determinant in designing translatable materials for efficient tissue regeneration with forthcoming impact expected in the treatment of bone defects.